Aldosterone antagonism in heart failure - Miller, Alan B (Dove Medical Press, 2007)
Aldosterone, a neurohormone known to affect electrolytes, has recently been implicated as playing a major role in the progression of heart failure, particularly in patients with systolic dysfunction. Major clinical trials designed to analyze clinical outcomes using an aldosterone antagonist have been done in two groups with heart failure. The first was the Randomized Aldactone Evaluation Study, which was done in symptomatic chronic advanced heart failure patients and showed that an aldosterone antagonist, spironolactone, reduced mortality significantly compared with placebo. Very few of these patients were on standard therapy with beta blockade. Another study, the Eplerenone Post myocardial infarction Heart failure Efficacy and SUrvival Study (EPHESUS), done in post-myocardial infarction patients with heart failure, demonstrated a significant reduction in mortality and hospitalizations for patients randomized to the aldosterone antagonist eplerenone. These trial results provide the background for aldosterone antagonist therapy in chronic advanced heart failure patients as well as post-myocardial infarction heart failure patients with reduced ejection.